2018
DOI: 10.2147/jmdh.s152823
|View full text |Cite
|
Sign up to set email alerts
|

Patient perspectives of participating in the cardiac CopenHeartRFA rehabilitation program for patients treated with ablation for atrial fibrillation

Abstract: PurposeThe CopenHeartRFA trial was designed and conducted to explore the effects of rehabilitation on patients treated with ablation for atrial fibrillation (AF). It included a cardiac rehabilitation program consisting of physical exercise and psychoeducational consultations over 6 months. As part of the evaluation of the CopenHeartRFA trial, both quantitative and qualitative data were collected. The intervention was delivered by a multidisciplinary team.AimThis study aimed to understand the experience of pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 27 publications
3
15
0
1
Order By: Relevance
“…The results from this review indicate that participating in an intervention including an educational component can lower anxiety levels for patients up to 24 months after inclusion in an intervention. Qualitative findings support this finding, as patients having participated in an intervention including education confirmed that they needed support from health care professionals to move on 35 . One previously mentioned qualitative study evaluated participating in a rehabilitation programme for patients with AF including a psycho‐educational component 35 .…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…The results from this review indicate that participating in an intervention including an educational component can lower anxiety levels for patients up to 24 months after inclusion in an intervention. Qualitative findings support this finding, as patients having participated in an intervention including education confirmed that they needed support from health care professionals to move on 35 . One previously mentioned qualitative study evaluated participating in a rehabilitation programme for patients with AF including a psycho‐educational component 35 .…”
Section: Discussionsupporting
confidence: 57%
“…Qualitative findings support this finding, as patients having participated in an intervention including education confirmed that they needed support from health care professionals to move on 35 . One previously mentioned qualitative study evaluated participating in a rehabilitation programme for patients with AF including a psycho‐educational component 35 . Patients described that the psycho‐education (delivered either face‐to‐face or by telephone) was important to them as they still needed support to move on and health professionals helped them regaining confidence in their mental strength 35 .…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Experiences and perceptions of participants in the NeCR will be assessed through individual in-depth interview of a sample of 15–20 intervention group participants. Sampling will occur until theoretical saturation, which is expected to be reached by selection of 20% of the intervention participants [74, 75]. To maximize the sample variation, participants who have different responses to the NeCR in terms of the changes on their scores on the primary outcomes (0-35th percentile, >35th percentile and > 70% percentile of the score) will be recruited.…”
Section: Methodsmentioning
confidence: 99%
“…На основе данных исследования CopenHeartRFA S.S. Risom и соавт. провели качественный анализ причин/барьеров, снижающих участие больного с ФП после успешной катетерной аблации в программе кардиореабилитации [46]. Главная причина -боязнь возврата симптомов ФП, которые вновь могут изменить жизнь пациента.…”
Section: Atrial Fibrillation and Rehabilitation фибрилляция предсердиunclassified